Therapeutic targets and potential delivery systems of melatonin in osteoarthritis - Xiong, Zhilin; Peng, Guoxuan; Deng, Jin; Liu, Miao; Ning, Xu; Zhuang, Yong; Yang, Hua; Sun, Hong (Frontiers in Immunology, 2024)
Osteoarthritis (OA) is a highly prevalent age-related musculoskeletal disorder that typically results in chronic pain and disability. OA is a multifactorial disease, with increased oxidative stress, dysregulated inflammatory response, and impaired matrix metabolism contributing to its onset and progression. The neurohormone melatonin, primarily synthesized by the pineal gland, has emerged as a promising therapeutic agent for OA due to its potential to alleviate inflammation, oxidative stress, and chondrocyte death with minimal adverse effects. The present review provides a comprehensive summary of the current understanding regarding melatonin as a promising pharmaceutical agent for the treatment of OA, along with an exploration of various delivery systems that can be utilized for melatonin administration. These findings may provide novel therapeutic strategies and targets for inhibiting the advancement of osteoarthritis.